2017
DOI: 10.2174/0929867324666170303162935
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Strategies of Plant-derived Compounds for Diabetes Via Regulation of Monocyte Chemoattractant Protein-1

Abstract: Regarding the increasing number of diabetic patients yearly, the recent progress in the putative therapies needs to be summarized. This article underlines the significance and involvement of the chemokine MCP-1 in the development of obesity, type 2 diabetes, and diabetic complications, with an emphasis on the role of plant metabolites in the regulation of this chemokine and thus the role in the prevention or therapy of diabetes. We suggest that MCP-1 might be a molecular marker of type 2 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 130 publications
0
6
0
Order By: Relevance
“…Although there are a number of drugs that are approved for the treatment of obese patients, many of them were withdrawn due to the severe adverse events such as heart diseases and psychiatric disorders [ 9 ]. Meanwhile, recent studies demonstrated that consumption of food-derived bioactive components such as phenolic compounds is positively associated with reducing the risk of obesity and its associated chronic diseases with low toxicity [ 10 , 11 ]. Thus, creating new dietary treatments based on various bioactive components in food has been emerging as a new possible intervention against obesity [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although there are a number of drugs that are approved for the treatment of obese patients, many of them were withdrawn due to the severe adverse events such as heart diseases and psychiatric disorders [ 9 ]. Meanwhile, recent studies demonstrated that consumption of food-derived bioactive components such as phenolic compounds is positively associated with reducing the risk of obesity and its associated chronic diseases with low toxicity [ 10 , 11 ]. Thus, creating new dietary treatments based on various bioactive components in food has been emerging as a new possible intervention against obesity [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological studies have indicated an inverse association between fruit and vegetable intake and the risk of DM. Several dietary patterns consisting of combinations of different foods or food groups are beneficial for diabetes management [15]. Proper nutrition and diet are important factors in the prevention and management of DM.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the interaction between monocytes and endothelial cells, intracellular adhesion molecule‐1 and MCP‐1 are upregulated by activation of nuclear factor‐kappa B (NF‐πB). [ 68 ] Many studies reported that the proinflammatory cytokines such as MCP1, ICAM1 and TGF‐β1 are elevated in diabetic kidneys and can thus contribute to diabetic nephropathy. [ 12,13 ] It translocates from the cytoplasm to the nucleus and induces the expression of MCP1, ICAM1 and TGF‐β1, leading to inflammation, glomerulosclerosis and tubulointerstitial fibrosis.…”
Section: Discussionmentioning
confidence: 99%